Knowledge and procedures of medical personnel about infection prevention in patients with chemotherapy-induced neutropenia - Alharbi, Ftoon Saeed; alrasheedi, Kholood; albalawi, Wardah Salh; Alhumaid, Mohammed Salman; Alruqi, Abdullah Fehaid Fahad; Al qarafi, Abdulmonem Hassan; Alsurayhi, Shahad Ali; Buanz, Fai; AlSubaie, Khulud Saud; Al ramadan , Amani Abbas; Al Rashid, Abdulaziz Saeed; ALmihbash, Abdullah Ahmed; et al. (Journal of Posthumanism, 2024)
Background: Chemotherapy-induced neutropenia significantly increases the risk of life-threatening infections in cancer patients, necessitating stringent infection prevention measures by medical personnel. Despite established protocols, gaps in knowledge and procedural adherence among healthcare workers persist, impacting patient outcomes. This study aimed to assess the knowledge and practices of medical personnel regarding infection prevention in neutropenic patients. Methods: A descriptive cross-sectional study was conducted involving 120 nurses from ICU, internal medicine, and oncology departments in a tertiary care hospital. Data were collected using a validated, self-administered questionnaire assessing demographic details, knowledge levels, and procedural adherence. Descriptive and inferential statistics were employed for analysis. Results: The majority of participants (45%) demonstrated good knowledge of infection prevention, while 11.7% scored poorly. Contaminated hands (93.3%) and inadequate hand hygiene (91.7%) were identified as primary infection sources. Procedural adherence was high for hand hygiene (80%) and PPE use (70.8%), but lower for patient education (60%) and isolation precautions (65%). ICU nurses exhibited the highest knowledge levels (50%), whereas oncology nurses had the highest proportion of poor knowledge (15%).Conclusion: While medical personnel generally possess adequate knowledge of infection prevention, inconsistencies in practice—particularly in patient education and isolation—highlight the need for targeted training and institutional reinforcement. Strengthening these areas is critical to improving patient safety and reducing infection-related morbidity in neutropenic individuals.